Death‐specific rate due to asthma and chronic obstructive pulmonary disease in Iran. (16th April 2018) - Varmaghani, Mehdi; Kebriaeezadeh, Abbas; Sharifi, Farshad; Sheidaei, Ali; Rashidian, Arash; Moradi‐Lakeh, Maziar; Naghshin, Roozbeh; Moin, Mostafa; Mehdipour, Parinaz; Heidari, Elham; Gohari, Kimiya; Rezaei, Nazila; et al.
Abstract: Background and objective: Asthma and chronic obstructive pulmonary disease (COPD) could be considered as a major health problem in industrialized and developing countries. This study was designed to analyze the trends of mortality from asthma and COPD at national and subnational levels in Iran based on National Death Registry, from 2001 to 2015. Materials and methods: We used Death Registration System (DRS) as the basic source of data. Death Registration System data were available from 1995 to 2010 in Iran's Ministry of Health. Although, Tehran and Isfahan, 2 most populated cities in Iran, had independent death registry systems in their cemeteries, by combining their data we achieved more comprehensive and representative data on death among Iranian people. We addressed incompleteness and misclassification of death registry system using demographic and statistical methods. We also employed spatio‐temporal and Gaussian process regression to extrapolate and interpolate mortality rates for the missing data. Results: Age‐standardized asthma mortality rate was 7.2 (5.6‐9.2) in females and 8.8 (6.9‐11.1) in males at the national level in 2015. Age‐standardized COPD mortality rates in females and males, respectively, were 8.46 (6.6‐10.9) and 12.38 (9.8‐15.6) during the studied years. A reduction in age‐standardized asthma mortality was observed during the period of study. In addition, the trend of COPD mortality was increasing. Conclusions: It seems that mortality rate attributable to COPD has risen during the past 15 years in Iran. It could have increased because of increased exposure of people to related risk factors such as air pollution which is a common problem in larger cities and border provinces.